Gender effects of the COVID-19 pandemic in the Swiss labor market - Corinne Dubois; Luisa Lambertini; Yu Wu (Swiss Journal of Economics and Statistics, 2022)
Abstract We study the impact of the pandemic on gender gaps in labor market outcomes in Switzerland. Using the Swiss Labor Force Survey data, we document a significant increase in the gender gap in labor market participation. We find no evidence of a worsening of the unemployment gender gap during the pandemic, but we find that women were more likely to uptake short-time work (STW). Unlike the USA, the presence of children in the household did not worsen labor gender gaps. Sector and occupation, however, play an important role in explaining gender gaps. In particular, we document substantial heterogeneity in the effect of the pandemic on participation, STW, hours worked, and wage outcomes depending on the availability of telework in the respondent’s occupation.